"I Made It Work": How Using a Self‐Assembled Product Increases Task Performance. Issue 3 (7th July 2021) - Köcher, Sören; Wilcox, Keith
Abstract : Although it is well established that consumers have an increased valuation for self‐assembled products, less is known about how using such products influences objective consumption outcomes. Across three experiments, the current research demonstrates that consumers perform better on tasks when they use a product they have self‐assembled—as opposed to an identical but ready‐to‐use product. We show that this effect results from an increase in self‐efficacy and rule out possible alternative accounts (i.e., product efficacy beliefs, performance motivation, feelings of psychological ownership, and product liking). In addition, we demonstrate that the self‐assembly effect emerges only when consumers actually use the self‐assembled product, is robust when product assembly requires different amounts of time and effort, and is not merely the result of a question‐behavior effect. Theoretical contributions and opportunities for future research are discussed.